Whole-exome sequencing analysis identifies novel variants associated with Kawasaki disease susceptibility - Xing Zhang; Ying Sun; Lijuan Meng; Caixia Ye; Huifeng Han; Tiesong Zhang; Yue Feng; Jianxiao Li; Lifen Duan; Yanfei Chen (BMC, 2023)
Abstract Background Kawasaki disease (KD) is an acute pediatric vasculitis affecting genetically susceptible infants and children. Although the pathogenesis of KD remains unclear, growing evidence links genetic susceptibility to the disease. Methods To explore the genes associated with susceptibility in KD, we applied whole-exome sequencing to KD and control subjects from Yunnan province, China. We conducted association study analysis on the two groups. Results In this study, we successfully identified 11 significant rare variants in two genes (MYH14 and RBP3) through the genotype/allele frequency analysis. A heterozygous variant (c.2650G > A, p.V884M) of the RBP3 gene was identified in 12 KD cases, while eight heterozygous variants (c.566G > A, p.R189H; c.1109 C > T, p.S370L; c.3917T > G, p.L1306R; c.4301G > A, p.R1434Q; c.5026 C > T, p.R1676W; c.5329 C > T, p.R1777C; c.5393 C > A, p.A1798D and c.5476 C > T, p.R1826C) of the MYH14 gene were identified in 8 KD cases respectively. Conclusion This study suggested that nine variants in MYH14 and RBP3 gene may be associated with KD susceptibility in the population from Yunnan province.